Operações urbanas consorciadas em São Paulo : prevalência dos interesses econômicos - Narita, Beatriz Sakuma (2020)
This dissertation aims to perform a critical analysis of the political and legal institute Consortium Urban Operation. Created in São Paulo during the 1990’s, the CUO was later included in the City Statute as one of the legal and political institutes capable of enabling the implementation of urban policies. The paper assumes that the CUO is unable to meet constitutional principles and guidelines for urban policy, because it is an instrument conceived with the purpose of creating new expansion spaces for the real estate market. In order to demonstrate this thesis, the paper presents how the Brazilian state approached the urban issue until it culminated in the promulgation of the Federal Constitution of 1988 and the City Statue. In addition, it analyzes the concept, the legal nature and the instrumentalization of the Consortium Urban Operation to present and discuss all the existing CUOs in the city of São Paulo. It concludes, then, that only the Operations located in areas of high interest of the real estate market presented positive economic results. However, by aesthetically transforming the urban landscape with upscale commercial and residential buildings, the CUOs were unable to harmoniously integrate these regions with the rest of the city, highlighting the existing problems of urban inequality. Finally, the research seeks to demonstrate that, in view of the changes made by the Strategic Master Plan of 2014, from São Paulo’s capital, there is a preference for the use of other instruments rather than the CUOs to enable the implementation of urban policy.